2015
DOI: 10.1016/j.crvi.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

ISSR-based analysis of genetic diversity among sorghum landraces growing in some parts of Saudi Arabia and Yemen

Abstract: Inter simple sequence repeats (ISSR) analysis was used to determine the genetic diversity among 15 genotypes of sorghum [Sorghum bicolor (L.) Moench] growing in some parts of Saudi Arabia and Yemen. A total of 92 alleles were amplified, with an average of 13 ISSR alleles per primer. Cluster analysis divided the 15 genotypes into two main groups. Group A consisted of five genotypes with white grains from Jazan and Abha with a similarity coefficient range of 0.527 to 0.818. Group B was comprised of 10 genotypes;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For effective sorghum breeding, advanced methods in molecular marker-assisted selection should be exploited. So far, SSR (Shehzad et al 2009 ), SNP (Luo et al 2016 ), RAPD (Akhare et al 2008 ), and ISSR (Basahi 2015 ) markers have been developed for sorghum. From these markers, SNPs have been the most intensively studied in sorghum as far as salt tolerance and yield are concerned.…”
Section: Molecular Markers As Potential Selection Toolsmentioning
confidence: 99%
“…For effective sorghum breeding, advanced methods in molecular marker-assisted selection should be exploited. So far, SSR (Shehzad et al 2009 ), SNP (Luo et al 2016 ), RAPD (Akhare et al 2008 ), and ISSR (Basahi 2015 ) markers have been developed for sorghum. From these markers, SNPs have been the most intensively studied in sorghum as far as salt tolerance and yield are concerned.…”
Section: Molecular Markers As Potential Selection Toolsmentioning
confidence: 99%
“…While, they were lower to those obtained in other studies with ISSRs, such as those of Pandian et al [43] in sorghum "Sorghumsp. ", Basahi et al [44] and Subhojit et al [45] in faba bean "Vicia faba" and lentil "Lens culinaris", and Dagnew et al [46] in Phaseolus vulgaris. These results showed that the greatest degree of polymorphism among the 24 accessions proved the capacity of the ISSR marker to study the evaluation of genetic variability between close genotypes of identical or different geographic origin.…”
Section: Pisum Genusmentioning
confidence: 99%
“…Another study suggested the use of ISSR markers to detect phenotypic variation amongst 15 genotypes of Sorghum landrace grown in Saudi Arabia and Yemen. In this case, eight genotypes of Sorghum bicolor were successfully differentiated into two clusters, one with dark grains and the other with white grains (Basahi, 2015). Recently, Al-Ameri et al (2016) used ISSR markers for the early sex determination of date palms in Saudi Arabia.…”
Section: Standard Molecular and Genomic Techniques In Plant Biodiversmentioning
confidence: 99%